Atanassov’s Intuitionistic Fuzzy Translations of Intuitionistic Fuzzy Subalgebras and Ideals in BCK/BCI-Algebras - Senapati, Tapan; Bhowmik, Monoranjan; Pal, Madhumangal; Davvaz, Bijan (Eurasian Mathematical Journal, 2015)
In this paper, the concepts of intuitionistic fuzzy translation to intuitionistic fuzzy subalgebras and ideals in BCK/BCI-algebras are introduced. The notion of intuitionistic fuzzy extensions and intuitionistic fuzzy multiplications of intuitionistic fuzzy subalgebras and ideals are introduced and several related properties are investigated. In this paper, the relationships between intuitionistic fuzzy translations and intuitionistic fuzzy extensions of intuitionistic fuzzy subalgebras and ideals are investigated.